Effects of biochar, ligneous soil amendments, and a microbial stimulant on soil biological activity, and carbon content and stability after two-years of their application in a boreal cropland - Heinonsalo, J.; Peltokangas, K.; Barré, P.; Baudin, F.; Cécillon, L.; Kalu, S.; Kanerva, S.; Karhu, K.; Kulmala, L.; Liski, J.; Salonen, A.-R.; Shrestha, R.; et al. (Elsevier, 2025)
The concerns for soil health and climate change have initiated actions to slow down soil carbon loss. The activities, collectively known as carbon farming, encompass various practices that seek to mitigate climate change and improve soil health. Among these practices, biochar alongside crop cultivation has been recognized as having potential for mitigating climate change. However, in heavily forested countries there is a wide variety of other carbon-rich side streams from the forest industry that could be utilized as organic soil amendments, or as microbial stimulants but their climate change mitigation potential, as well as the mechanisms underlying their observed effects on soil health, are not yet fully understood. The aim of this study was to assess and compare the use of various wood-based, i.e. ligneous soil amendments and a stimulant that could be used alongside conventional farming practices in a field experiment to boost soil biological activity and carbon sequestration. The studied treatments included two biochar (Salix sp. and Picea abies), two pulp mill sludge, and one microbial stimulant treatment. The economically relevant application rates of the amendments ranged from 9000 to 21900 kg/ha (on dry weight basis) and they were applied once, whereas the microbial seed stimulant was used yearly. We investigated their impacts on soil organic carbon content and its stability, as well as on soil microbial abundance, activities, and community structures. Based on the extensive data we collected, mainly biochars increased soil organic carbon content enough to be detectable after two years. In contrast, non-biochar amendments did not have the same effect on soil carbon, likely due to smaller application rates and higher decomposition rates. On the other hand, both the sludge and biochar treatments led to an increase in soil pH, but the observed changes in soil chemical properties had little impact on soil microbiology. Microbial stimulant was shown to be ineffective and did not alter soil biology as expected. Overall, the studied amendments had no detectable negative effects on measured soil physico-chemical parameters and had a marginal positive impact on soil biology. This suggests that these amendments could be promising options for recycling ligneous side streams from the forest industry to support primary production in arable fields.
Keywords: organic soil amendments; microbial stimulant; biochar; pulp mill sludge; soil organic carbon; soil microbiology